The Important Role of the Nusantara Module Activities in the Independent Student Exchange Program - Anatalisya Ari Naibaho; Uci Ekaristi Sembiring; Lia Deniati Manurung; Elza L.L. Saragih; Andriono Manalu (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Merdeka Student Exchange Program is a one-semester student mobility program to gain learning experience at public and private universities in Indonesia while at the same time strengthening unity in diversity. The method used in this study is a descriptive qualitative approach which aims to (1) Create a general understanding of diversity tolerance, diversity, inspiration, and social contributions designed through the archipelago module activities. (2) understand students' perspectives on phenomena by gathering information and documenting the Nusantara module activities completed by students. The subjects of this study were students who were placed at the Siliwangi Teaching and Education Institute (IKIP Siliwangi) in the Independent Student Exchange program. The results of the study show the tolerance attitude of students towards ethnicity, religion, culture and customs through an attitude of respect and respect for ethnicity, religion, culture and customs.